A Facile Study concerning the Legal Issues and Challenges of Herbal Medicine in Nigeria - Paul Atagamen Aidonojie; Esther Chetachukwu Aidonojie; Oaihimire Idemudia Edetalehn; Oluwaseye Oluwayomi Ikubanni; Alade Adeniyi Oyebade (The Indonesian Journal of International Clinical Legal Education, 2022)
It is apt to state that there have been an increase and the threat of contagious communicable and non-communicable diseases within most countries and Nigeria in particular. The causes of the outbreak are a result of an unhealthy lifestyle and poor scientific laboratory management. However, in search for finding a cure, has resulted in most people relying on herbal products. In this regard, the increasing demand for the herbal products has resulted in unskilled individuals indulging in the production of herbal products. It is concerning this pharmaceutical abnormality that this study tends to utilize a hybrid method of study in ascertaining the dangers, guidelines, and legal regulations concerning poorly processed and manufactured herbal products. In this regard, the study, therefore, employs the use of a hybrid method of research to ascertain if there is compliance with international ethics and guidelines concerning herbal medicine production. An online questionnaire was sent to 313 respondents residing in Nigeria. The study, therefore, found that most individual indulging in herbal medicine production does not observe the international and national ethical guidelines concerning the manufacturing of herbal medicine. The study therefore concluded and recommended that there is a need for the Nigerian Government to through an effective legal framework and regulatory body address scientific and legal issues as it concerns the whole process involved in the production of herbal products.